Feasibility of using Problematic Aquatic Weeds in Productive Manner by Generating Vermicompost in Coconut Triangle Area of Sri Lanka - Senarathne, S. H. S.; Dayananda, H. N.; Atapattu, A. A. A. J.; Raveendra, S. A. S. T. (International Coconut Community, 2017)
Aquatic weeds cause severe productivity loss in agriculture. These plants invade lakes, ponds, rivers, canals and agricultural fields, becoming noxious weeds. The study was conducted at the vermicomposting unit of the Coconut Research Institute, Lunuwila, in the Low country Dry Zone of North Western province of Sri Lanka from August 2012 to May 2013 to find out the feasibility of producing vermicompost from three aquatic weeds; Salvinia molesta, Eichhornia crassipes and Lagenandra toxicaria. Vermicompost and compost were prepared separately from aquatic weeds and Gliricidia and Guinea grass combinations. During the vermicomposting process, growth parameters of earthworms; number of earthworms, was taken in every ten days interval further, physical, chemical and biological properties of compost and vermicompost were analyzed. Experiment was carried out in a Complete Randomized Design (CRD) with eight treatment and five replicates in each treatment. Eichhornia and Salvinia recorded the highest adult earthworm number and juvenile number with the lowest mortality rate. Electrical conductivity (6.75 dSm-1), organic carbon (13.21%), phosphorous (3.61%), potassium (5.03%) and calcium (6.12%) were significantly high in Lagenandra toxicaria, Gliricidia and Guinea grass treatment was significantly high in nitrogen content (3.93%) and low in C: N ratio (2.51), compared to aquatic weeds. Salvinia showed comparatively higher nitrogen content and lower C: N ratio among aquatic weeds. Both Eichhornia and Lagenandra showed significantly higher microbial activity. Vermicompost was superior in all the properties compared to compost in the same substrate. The study revealed that aquatic weeds such as Salvinia molesta, Eichhornia crassipes and Lagenandra toxicaria which are readily available in the coconut triangle can be successfully used to produce Vermicompost. It can be concluded that the Vermicompost produced from aquatic weeds locally could be a suitable organic fertilizer for organic coconut farming in Sri Lanka.